Transformadores trifásicos: comparativo de materiais para os enrolamentos - Ballan, André Felipe Matzenbacher (2019)
In recent years copper prices has been increasing in relation to aluminum, so it is important to evaluate and compare the costs of manufacturing copper and aluminum equipment. One of the equipment that has the possibility of replacing its copper parts with aluminum is the transformer. This present in applications of low power electronics up to power transmission systems. Compared to copper, aluminum has more resistance, therefore, lower conductivity. Thus, a study is required for the use of aluminum in the manufacture of windings of three-phase low-power transformers. It must assess whether aluminum is capable of meeting the same working conditions as copper. The present work has the objective of carrying out a comparative study of these materials in the use of windings of three - phase transformers. In this way the design of a transformer with copper windings and another one with aluminum windings was developed, being the calculations realized in a software of mathematical calculation, it was noticed that the design with aluminum coils had performance equivalent to design with copper coils, in addition aluminum has economic advantages over copper. For a future work is aimed at the construction of the appropriate transformers.